The 5E instructional model and the teaching of Chemistry: definitions and strategies (Research, Society and Development, 2022)
The global health crisis brought challenges to society as a whole and to education in particular. The distance learning approach, still far from the admiration and unanimity of educators, started being presented as an emergency solution during the pandemic context, and all teachers were called upon to somehow get involved with the strategies of this teaching modality. Today, the use of digital information and communication technologies in the school context is an undeniable reality at all levels of schooling, which has caused significant changes in the modus operandi of the educational system and the routines of teachers and students. The barriers between physical and virtual spaces are increasingly being broken down and, following the technological escalation, the means to conduct, learn, interact, create, and establish relationships between teachers and students, as well as between the students themselves, are being redefined. The classroom is no longer the same, and, without wishing to be prophetic, it may never be exactly what it was. This work was carried out during the initial critical days of the pandemic in private schools in São Luís (MA), during high school chemistry classes, and seeks to highlight the importance and potential of the 5E instructional method (Engage, Explore, Explain, Elaborate, Evaluate) for motivating teaching and learning. The methodology used was qualitative in nature and data collection was carried out through observation during the classes.